Przepisywanie PRL-u. Strategie przywoływania przeszłości w najnowszym kinie polskim - Żyto, Kamila (Załącznik Kulturoznawczy, 2024)
Interest in the memory of the Polish People’s Republic and the ways it is articulated is constantly increasing. The number of films and series set in the communist era is growing. There is also a significant drive to rewrite the past of the Polish People’s Republic, that is, to shape stories set in those years in accordance with the conventions and thematic preferences significant for the contemporary pop culture genre. The article indicates strategies adopted by Polish filmmakers while portraying Polish People's Republic. The concept of prosthetic memory as a form of post-memory is introduced to analyze the phenomenon.